Can Corporate Social Responsibility (CSR) mitigate political risk among European firms? - Bhuiyan, Sabbir Ahmed (My University, 2025)
Growing political instability has led firms and scholars to rethink the role of non-market strategies, particularly corporate social responsibility (CSR), in addressing risk at the firm level. Political disruption—a rapid change in regulations, reversal of policies, and general instability of the environment—is a weighty threat to performance, especially where capital markets are concerned. While the finance and management literature has made considerable strides in its exploration of the financial implications of CSR, empirical evidence on whether it actually can serve as a CSR insurance policy against political risks is scanty and not definitive. To fill this void, this paper makes an attempt to examine whether involvement in CSR does really reduce stock-return volatility during periods of political turbulence for publicly traded companies in Europe. Based on stakeholder theory, the study defines CSR not only as a mechanism of ethics or reputation but as a proactive and strategic part of corporate risk management. The paper uses an unbalanced panel dataset of 419 firms from the STOXX 600 index for the period between 2010 and 2022 to verify two hypotheses. First, study the direct effect that CSR engagement has on stock-return volatility. Second, analyze how CSR moderates the relationship between firm-level political risk and volatility. This report uses a regression model with firm and year fixed effects, controlling for important financial and structural factors such as firm size, leverage, profitability, earnings per share, and market-to-book ratio. The empirical results strongly support both hypotheses. Firms with higher CSR engagement show lower stock-return volatility; political risk is harmed through the channel of affecting CSR firms' performance. Indeed, the interaction between CSR and political uncertainty means that in times of external political shocks, CSR serves as a resilience-enhancing mechanism for firms. This has robustly held across multiple model specifications and subsample analyses. This study adds to the CSR and political risk management bodies of literature by providing evidence that volatile political environments can make CSR a strategic asset. Hence this study underscores the practical significance of CSR not only in fortifying stakeholder relationships but also in building financial stability. For corporate managers, this finding stresses the need to integrate CSR into the core business strategy as a tool for mitigating risks. For policymakers, this result is evidence-based advocacy for promoting socially responsible business practices as a pathway to institutional and economic resilience.
Keywords: societal responsibility; risks; risk management; corporate responsibility; uncertainty; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance